2020
DOI: 10.3892/br.2020.1349
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing‑based identification of potential targets in acute myeloid leukemia: A case report

Abstract: Acute myeloid leukemia (AML) refers to heterogenous types of blood cancer which possess a complicated genomic landscape, and multiple novel mutational alterations are frequently being reported. Herein, a case report of a 37-year old AML patient is presented, who was diagnosed following laboratory investigation after admission. The patient had thrombocytopenia, and three consecutive blast counts of 40, 30 and 41%, respectively. A blood sample was collected for whole-genome RNA sequencing to understand the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…SNP and mutation analyses revealed a significant number of genetic variations [ 13 ]; the number of novel transcripts is summarised in Table 2 . Among them, exonic NRAS mutations, intronic mutations in nucleophosmin ( NPM1 ), and intronic and exonic mutations in fms-like tyrosine kinase 3 ( FLT3 ) have been detected [ 13 ]. It was previously reported that specific mutations in NPM1 , NRAS and FLT3 are common genetic signatures in AML [ 14 , 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…SNP and mutation analyses revealed a significant number of genetic variations [ 13 ]; the number of novel transcripts is summarised in Table 2 . Among them, exonic NRAS mutations, intronic mutations in nucleophosmin ( NPM1 ), and intronic and exonic mutations in fms-like tyrosine kinase 3 ( FLT3 ) have been detected [ 13 ]. It was previously reported that specific mutations in NPM1 , NRAS and FLT3 are common genetic signatures in AML [ 14 , 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Routine haematology investigations and cytogenetic reports have been revisited in our previous publication. 1 In brief, cytogenetics revealed 47, XX, +8[18]/46, XX[1] karyotype and 88% trisomy 8 with RUNX1 partner transcriptional corepressor 1 (RUNX1T1) abnormality, both of which are characteristics of AML. A post-treatment bone marrow aspirate on 25/9/2018 showed a marked suppression of trilineage haematopoiesis with a relative increase in lymphocytes and macrophages.…”
Section: Case Presentationmentioning
confidence: 99%
“…Acute myeloid leukaemia (AML) is a haematological malignancy characterised by sophisticated, heterogeneous genomic signatures, making its clinical management quite challenging (reviewed in 1 ). In this respect, genetic abnormalities are associated with disease prognosis and decisions on targeted therapies for patients.…”
Section: Introductionmentioning
confidence: 99%